AUDITING: FORMATION AND DEVELOPMENT IN TERMS OF MARKET RELATIONS (World Economics and Finance Bulletin, 2023)
The article focuses on raising the status of the most qualified audit specialists to the status of independent international auditors. It is noted that this will give an idea of the uniqueness and the possibility of solving certain problems of improving the social orientation of the ongoing transformations in the course of the development of the innovative economy. It is also noted that the effectiveness of the audit, all other things being equal, is directly proportional to the degree of independence of the auditor from the management of the organization to which he provides professional control services. Independent audit firms should be able to solve certain specific problems of their self-development.